Chemotherapy for transarterial chemoembolization in patients with unresectable hepatocellular carcinoma - Wu, Jie (Baishideng Publishing Group Inc, 2014)
AIM: To compare the efficacy of different chemotherapeutic agents during conventional transarterial chemoembolization (cTACE) in the treatment of unresectable hepatocellular carcinoma (HCC). METHODS: A retrospective review was undertaken of patients with unresectable HCC undergoing cTACE from May 2003 to November 2011. A total of 107 patients were treated with at least one cTACE session. Irinotecan (CPT-11) was used as a chemotherapeutic agent in 24 patients, gemcitabine (GEM) in 24 and doxorubicin in 59. RESULTS: The time to progression and overall survival rates were significantly superior in patients treated with CPT-11 compared with the GEM or doxorubicin treated groups (11.4, 8.2, 9.5 mo, P = 0.02 and 21.7, 12.7, 14.5 mo, P = 0.004, respectively). Subgroup analysis showed that for intermediate-stage HCC, CPT-11 resulted in a significantly longer time to progression and overall survival compared with the GEM or doxorubicin treated groups (P = 0.022; P = 0.003, respectively). There were no significant differences in adverse events among the three groups (P > 0.05). CONCLUSION: For patients treated with cTACE, the chemotherapeutic agent CPT-11 was significantly associated with improved overall survival and delayed tumor progression compared with GEM or doxorubicin. There were no significant differences in clinical adverse events between the three agents. CPT-11 thus appears to be a promising agent when combined with cTACE for the treatment of HCC.